Pengelolaan Hutan Mangrove dan Daya Tariknya Sebagai Obyek Wisata di Kota Probolinggo - Wiyono, Mardi (Jurnal Aplikasi Manajemen, 2009)
Be present mangrove forest pressured by human needs, then mangrove forest be decrease. The mangrove forest have much function, it is enduring abrasive, as habitat of sea, etc. The research method use to descriptive method. Collecting data be conducted with observation, interview, and documentation technique. The research result show that Probolinggo City have mangrove forest 74.68 Ha, covered: 6.13 Ha at Ketapang Village, 19.34 Ha at Mangunharjo Village, 12.30 at Mayangan Village, 20.09 at Pilang Village, and 16.82 at Sukabumi Village. The mangrove village at Probolinggo have been degradation (42%). However, the mangrove forest at Probolinggo have potential for ecotourism, and supported by another facilities and natural potential at environmental of Probolinggo City.